Peroxiredoxin 2 mediates insulin sensitivity of skeletal muscles through regulation of protein tyrosine phosphatase oxidation. (June 2018) - Kim, Jung-Hak; Park, Sun-Ji; Chae, Unbin; Seong, Joongbae; Lee, Hyun-Shik; Lee, Sang-Rae; Lee, Seunghoon; Lee, Dong-Seok
Graphical abstract: Abstract: Insulin signaling is essential for regulating glucose homeostasis. Numerous studies have demonstrated that reactive oxygen species (ROS) affect insulin signaling, and low ROS levels can act as a signal to regulate cellular function. Peroxiredoxins (Prxs) are highly abundant and widely expressed antioxidant enzymes. However, it is unclear whether antioxidant enzymes, such as Prx2, mediate insulin signaling. The aim of our study was to investigate the influence of Prx2 deficiency on insulin signaling. Our western blot results showed that Prx2 deficiency enhanced insulin signaling and increased oxidation of protein tyrosine phosphatase 1B (PTP1B) and phosphatase and tensin homologue (PTEN) in mouse embryonic fibroblasts (MEFs) treated with insulin. In addition, we assessed ROS levels with a Cytosol-HyPer H2 O2 sensor. As a result, increased ROS levels and Akt activation were decreased by N -acetyl-cysteine (Nac), which acted as an antioxidant in Prx2-deficient MEFs. Body weight measurements and glucose tolerance test (GTT) revealed significant body weight reduction and increase in glucose clearance in Prx2 -/- mice fed a high-fat diet. Interestingly, glucose transporter type 4 (GLUT4) was significantly higher in Prx2 -/- mice than in wild-type mice according to western blotting results. Western blotting also revealed that Akt phosphorylation was higher in Prx2 -/- MEFs and muscle tissue than in wild-type. Together, our findings indicate that increased ROS due to Prx2 deficiency promotes insulin sensitivity and glucose clearance in skeletal muscles by increasing protein tyrosine phosphatase (PTPs) oxidation. These results provide novel insights into the fundamental mechanisms of insulin signaling induced by Prx2 deficiency and suggest that ROS-based therapeutic strategies can be used to suppress insulin resistance.